2011
DOI: 10.1016/j.acra.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Weighted Imaging in Predicting Progression Free Survival in Patients with Squamous Cell Carcinomas of the Head and Neck Treated with Induction Chemotherapy

Abstract: Background To assess the role of diffusion weighted imaging (DWI) in predicting progression-free survival in patients with squamous cell carcinomas of head and neck (HNSCC) treated with induction chemotherapy. Methods Eighteen patients with HNSCC underwent DWI studies prior to treatment and within 3-weeks after completion of induction chemotherapy. Median apparent diffusion coefficient (ADC) values were computed from the largest cervical metastatic lymph node. Percentage (%) changes in ADC values from pre-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…16 This result might be in line with the findings of Kim and associates of significant difference between complete and partial responders to chemoradiation therapy of pretreatment ADC values with b-values of 1,000 s/mm 2 20 and results of Kato's team showing an inverse correlation between tumor regression rate and ADC values. 19 However, King's group could not corroborate these positive results using a b-value of 500 s/mm 2 21,22 nor could Vandecaveye's team 23 using a b-value of 1,000 s/mm 2 .…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…16 This result might be in line with the findings of Kim and associates of significant difference between complete and partial responders to chemoradiation therapy of pretreatment ADC values with b-values of 1,000 s/mm 2 20 and results of Kato's team showing an inverse correlation between tumor regression rate and ADC values. 19 However, King's group could not corroborate these positive results using a b-value of 500 s/mm 2 21,22 nor could Vandecaveye's team 23 using a b-value of 1,000 s/mm 2 .…”
Section: Discussionsupporting
confidence: 80%
“…19 Berrak and colleagues showed significant difference in the percentage of change of ADC values of metastatic nodes before and after induction chemotherapy between live patients and patients who died of HNSCC, but they did not show any potential of pretreatment ADC values to predict outcome. 16 In this regard, our study showed the potential of pretreatment ADC values to reflect the treatment response to induction chemotherapy, which was not revealed in standard b-value DWI.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations